Program Peningkatan Militer Jepang di kawasan Asia Pasifik melalui NDPG (National Defense Program Guideline) pasca masuknya dukungan dari AS - Maheswara, Ida Bagus Gandhi; Susanti, Suksma; Fasisaka, Idin (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This thesis discusses the development of the Japanese Military Enhancement Program in the Asia Pacific region through NDPG after the inclusion of support from the US. This research will only focus on how the improvement of the Japanese military after the entry of US support succeeded in establishing cooperation with Japan. This paper uses two concepts, namely the concept of alliances and national interests. Both countries have a level of strength against the military. Japan itself is known to have power in Asia and the Pacific, while America has become the strongest military force in the world to date. The two countries then fellowship one of the objectives is to achieve their interests. Japan has become one of the focuses of this writing, where Japan is seeking assistance from the United States because of threats from surrounding countries. Keywords: NDPG (National Defense Program Guideline), Alliance, National Interest.